Effects of Early Physiotherapy Intervention for Head and Neck Squamous Cell Carcinoma – A Case Report. - Mitesh Kumar, Babulal; Arunachalam, Ramachandran; Rajkumar Krishnan, Vasanthi (TamilNadu Scientific Research Organisation, 2022)
To determine the effects of early physiotherapy intervention for head and neck squamous cell carcinoma. The purpose of this study is to describe early baseline characteristic for a consecutive patient who receives physical therapy with a complaints of temporomandibular dysfunction in head and neck squamous cell carcinoma patients . And also to describe pattern of changes in predicted clinical outcomes across physical therapy episodes of care and regular follow-up. This study helps to setup early physical therapy to improve the function of TMJ and muscles of mastication. The main symptoms that the patients suffer from restricted mouth opening, stiffness, fatigue, and pain of the jaw, severe swallowing and speech problem. positive findings of decreased TMJ joint ROM and cervical ROM. Patient has performed clinical functional evaluation with pre and post-treatment with the follow-up of about 3 months assessment. The therapy includes self trained normal jaw ROM with limited condylar rotation, active vertical mandibular movement, cold therapy, passive motion device, grades of joint distraction ,massage of masseter muscle. For pain intensity Numerical pain rating scales , 11cm plastic ruler marked in millimeters, inclinometer for cervical range of motion. CO- QOL questionnaire scale, Gothenburg trismus questionnaire. We concluded that the patients with oral squamous cell carcinoma were found to be effective in providing early physiotherapy intervention which improves ROM, muscle control and co-ordination to enhance the functional mobility.